Discrimination Narrative and Chinese Indonesians’ National Identity: Is There Any Correlation? - Ninawati Ninawati; Kurnia Setiawan; Meiske Yunithree Suparman (UM Purwokerto Press, 2021)
Chinese Indonesian have been often treated as an outsider within the Indonesian society. Such a situation had happened for a long time. The discriminative experience of Chinese Indonesian came in the form of racial stereotypes and prejudice. In this study, we analyze the correlation between the discrimination narrative and Chinese Indonesian’s national identity. We collected our data through a questionnaire and involved 126 students in Jakarta as our subjects. The questionnaire consists of a national identity variable composed of four dimensions, namely fundamental (6 items, reliability 0.675), instrumental (4 items, reliability 0.520), natural (4 things, reliability 0.798), actualization (4 items, reliability 0.639). Discrimination narrative variables consist of master narrative (10 items, reliability 0.832) and counter-narrative (8 items, reliability 0.781). The selection of those subjects was made using the convenience sampling technique. We employed the correlational method to analyze the data. Our analysis showed that master narrative was not correlated with National Identity with a p-value = 0.179 (> 0.05). Meanwhile, the narrative counter correlates with National Identity with a value of p = 0.008 (<0.05) and a correlation coefficient of 0.234. This means that if someone accepts a counter-narrative statement, it will add value to their National Identity.